Colon tumor mutations and epigenetic changes associated with genetic polymorphism: Insight into disease pathways - Slattery, Martha L. (2008)
Variation in genes associated with serum levels of proteins may be useful for examining specific disease pathways. Using data from a large study of colon cancer, we examine genetic variants in insulin, inflammation, estrogen, metabolizing enzymes, and energy homeostasis genes to explore associations with microsatellite instability (MSI), CpG Island methylator phenotype (CIMP), mutations of p53 in exons 5 through 8, and mutations in codons 12 and 13 of Ki-ras. Insulin-related genes were associated with CIMP positive and MSI tumors, with the strongest associations among aspirin users. The Fok1 Vitamin D Receptor (VDR) polymorphism was associated with CIMP positive/Ki-ras mutated tumors; the Poly A and CDX2 VDR polymorphisms were associated only with Ki-ras mutated tumors. NAT2 was associated with CIMP positive/Ki-ras mutated tumors but not with MSI tumors. The TCF7L2 rs7903146 polymorphism was associated with p53 mutated tumors. Most associations varied by recent aspirin/NSAID use: IL6 rs1800796 and rs1800795 polymorphisms were associated inversely with tumor mutations in the presence of aspirin/NSAIDs; POMC significantly reduced risk of Ki-ras- mutated tumors when aspirin/NSAIDs were not used; the TCF7L2 rs7903146 was associated with reduced risk of Ki-ras-mutated tumors in the presence of aspirin and increased risk in the absence of aspirin. These data, although exploratory, identify specific tumor subsets that may be associated with specific exposures/polymorphism combinations. The important modifying effects of aspirin/NSAIDs on associations with genetic polymorphisms reinforce the underlying role of inflammation in the etiology of colon cancer.